2013
DOI: 10.3390/plants2010057
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Anti-Cancer Cell Proliferation Properties of Natsuhaze (Vaccinium oldhamii Miq.), Shashanbo (V. bracteatum Thunb.) and Blueberry Cultivars

Abstract: Antioxidants are abundant in blueberries, and while there are many studies concerning the bioactive compound of fruit, it is only recently that the wild Vaccinium species has attracted attention for their diverse and abundant chemical components. The aim of this study was to investigate the bioactive compounds of blueberry cultivars and wild species found in Japan. Among the five extracts of the Vaccinium species, Natsuhaze (Vaccinium oldhamii Miq.) was found to be the most effective at inhibiting the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Antioxidants are abundantly present in the genus Vaccinium , and numerous studies have been focused on their antioxidant activity [59,60,61]. Berries of all important Vaccinium species ( V. macrocarpon , V. oxycoccos L., V. vitis-idaea L.) have been proved to possess a strong potential to prevent the free radical reactions from continuing [31,62].…”
Section: Antioxidant Activity Of Cranberry Fruitmentioning
confidence: 99%
“…Antioxidants are abundantly present in the genus Vaccinium , and numerous studies have been focused on their antioxidant activity [59,60,61]. Berries of all important Vaccinium species ( V. macrocarpon , V. oxycoccos L., V. vitis-idaea L.) have been proved to possess a strong potential to prevent the free radical reactions from continuing [31,62].…”
Section: Antioxidant Activity Of Cranberry Fruitmentioning
confidence: 99%
“…Unfortunately, as this paper did not indicate the species of blueberry, discussion of differences in physiological function between this study and previous studies in terms of species is limited. A number of species of blueberry occur in nature and Vaccinium virgatum Aiton used in this study has potent antioxidant activity and contains high levels of polyphenols (Tsuda et al 2013). Dietary polyphenols protect experimental animals from HFHSD-induced oxidative stress and prevent HFHSDinduced glucose metabolism disruption (Lee et al 2009, FeilletCoudray et al 2009, Hanhineva et al 2010.…”
Section: -Week-old Otsuka Long-evans Tokushima Fatty (Oletf) Rats;mentioning
confidence: 99%
“…Massarotto Superfood and Functional Food -An Overview of Their Processing and Utilization et al [142] demonstrated that anthocyanins and other phenolic compounds have cytotoxic activity, as tested in tumoral cell lines under in vitro conditions; thus, blueberry extracts could be useful for future treatment of cancer, as a natural cytotoxic agent. In this context, Tsuda et al [143] obtained similar results with human leukemia cells and ethanolic extracts of several berries that include blueberry fruits. In all cases, the induction of apoptosis in the cancerous cells may be the mechanism triggered by blueberry.…”
Section: Highbush Blueberry (Vaccinium Corymbosum L)mentioning
confidence: 70%